Les instruments conceptuels de la patrimonialisation du paysage et de la nature dans l’Europe de la Belle Époque - Luigi Piccioni (Projets de Paysage)
The “heritagisation” of the landscape dates back to the last decades of the 19th century. The phenomenon may be studied either as a part of the strong nationalist movement of the period or as a part of the emergence of environmentalism. At the European level, the nascent movement for the protection of nature shared a fundamental concern for the historical and artistic dimensions of natural phenomena and defined concepts for their preservation. In the article we describe the meaning of some of these concepts and the use that was made of them at the time, namely the landscape, the site, the natural monument, the picturesque site, and natural beauty.